تعميم القاعدة عند ابن تيمية في باب المبتدأ والخبر ونواسخهما: Ta’mīm al-Qā’idah ’inda Ibn Taimiyyah fi Bāb al-Mubtada wa al-Khabar wa Nawāsikhiha - Gumilar, Rizki; Dawy, Ebrahim (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
لم تتوقف جهود العلماء لتبسيط قواعد اللغة العربية مع مرور الزمن. وهذا هو شأن من يعتبر خبيرًا في مجال العقيدة، وهو ابن تيمية. يهدف هذا البحث إلى كشف استخدام منهج "تعميم القواعد" في شرح أحد الأبواب المهمة في النحو العربي، وهو المبتدأ والخبر ونواسخهما. والمنهج المستخدم في هذا البحث هو المنهج الوصفي التقعيدي، وهو يتم من خلال جمع المعلومات اللازمة من المصادر الأساسية، واستخراجها، وعرضها في النتائج المقترحة. ومن الاستنتاجات التي توصل إليها هذا البحث أن اتحاد العامل لما اتحد فيه المعنى، ويعمل العامل الواحد في ما اتحد فيه المعنى، فعامل النعت هو عامل المنعوت ذاته، وعامل الحال هو الذي يعمل في صاحبها، وكذلك عامل الخبر هو نفس العامل في المبتدأ، ومع هذه القاعدة سوف يحفظها الطلاب ويفهمونها بسهولة. والمساهمة التي يرجى الوصول إليها فهم باب المبتدأ والخبر ونواسخهما لدى الطلاب بأسهل طرائق، ولهذا البحث أيضًا مساهمة في تطوير الأساليب لتدريس قواعد اللغة العربية بشكل عام. Abstract Scholars’ efforts to simplify Arabic grammar rules have persisted over time. This is also true for Ibn Taymiyyah, a notable expert in the field of Islamic theology. This research aims to apply the "rule generalization" method to explain one of the important aspects of Arabic syntax, namely Mubtada’ and Khabar, and their modifiers. The methodology used in this research is the descriptive rule-based approach, which involves collecting necessary information from primary sources, extracting it, and presenting it in the proposed results. Among the result reached by this research is that the ‘amil is united in what the meaning is united in, and one ‘amil work in what the meaning is united in. The ‘amil of na’at is the ‘amil of man’ut itself, and the ‘amil of haal is the one that acts on shaahib haal, and likewise, the predicate ‘amil of khabar is the same ‘amil of mubtada, and with this, the rule will be easily memorized and understood by students. The anticipated contribution of this research is to facilitate students’ comprehension of the Mubtada’, Khabar, and their modifiers in the simplest ways possible. Additionally, this research aims to contribute to the development of methods for teaching Arabic grammar rules in general.